Question
upstudy study bank question image url

The function \( f(x)=(x+8)^{5} \) is one-to-one. a. Find an equation for \( f^{-1}(x) \), the inverse function. b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \). B. \( f^{-1}(x)= \), for \( x \geq \) C. \( f^{-1}(x)=\sqrt[5]{x}-8 \), for all \( x \) b. Verify that the equation is correct. \( f\left(f^{-1}(x)\right)=f(\square) \) for \( x \leq \) \( =\square \) and \( \quad f^{-1}(f(x))=f^{-1}(\square) \) Substitute. Simplify.

Ask by Rojas Riley. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**a.** The inverse function is \( f^{-1}(x) = \sqrt[5]{x} - 8 \) for all real \( x \). **b.** Verification: \[ f(f^{-1}(x)) = x \quad \text{and} \quad f^{-1}(f(x)) = x. \]

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Bonus Knowledge

To find the inverse function \( f^{-1}(x) \) of \( f(x) = (x + 8)^{5} \), we start by letting \( y = f(x) \). This gives us the equation \( y = (x + 8)^{5} \). To find the inverse, we solve for \( x \) in terms of \( y \): 1. Rewrite the equation: \( y = (x + 8)^{5} \). 2. Take the fifth root of both sides: \( \sqrt[5]{y} = x + 8 \). 3. Isolate \( x \): \( x = \sqrt[5]{y} - 8 \). Thus, the inverse function is \( f^{-1}(x) = \sqrt[5]{x} - 8 \) for all \( x \). Next, we must verify that our inverse function is correct by proving that \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \). To start with \( f(f^{-1}(x)) \): 1. Substitute \( f^{-1}(x) \) into \( f \): \[ f(f^{-1}(x)) = f(\sqrt[5]{x} - 8) = ((\sqrt[5]{x} - 8) + 8)^{5} \] Simplifying this, we get: \[ = (\sqrt[5]{x})^{5} = x. \] Now, let's check \( f^{-1}(f(x)) \): 1. Substitute \( f(x) \) into \( f^{-1} \): \[ f^{-1}(f(x)) = f^{-1}((x + 8)^{5}) = \sqrt[5]{(x + 8)^{5}} - 8. \] Simplifying gives us: \[ = (x + 8) - 8 = x. \] Both verifications show that \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \), confirming that we have the correct inverse function. To fill in the blanks: B. \( f^{-1}(x)= \sqrt[5]{x}-8 \), for \( x \geq (8^5) \) C. \( f^{-1}(x)=\sqrt[5]{x}-8 \), for all \( x \) b. Verify that the equation is correct: \( f\left(f^{-1}(x)\right)=f(\sqrt[5]{x}-8) \) for \( x \leq (8^5) \) \( = x \) and \( \quad f^{-1}(f(x))=f^{-1}((x+8)^5) \) Substitute. Simplify \( = x \).

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy